Pilot : navigating personhood within science fiction : a thesis presented in partial fulfilment of the requirements for the degree of Master of Design in Illustration at Massey University, Wellington, New Zealand - Moore, Bo (Massey University, 2016)
Representations of the 'other' in media often exist only to further the narratives of the 'dominant' for the benefit of an assumedly-dominant audience, and are otherwise unseen or misrepresented. This results in the other being denied genuine reflections of themselves at a social and cultural level (Diaz as cited in Donahue, 2009). Through visual analysis and design, this research explores the nature of the term personhood - defined as character and qualities regarding who can be a ‘person’ - through media representations of both the human other and the fictional alien other. The alien within science fiction is visible as a reaction to our very human history of colonialism (Diaz, 2014) and in particular to the categorization of the human and non-human other. The resulting characterisation, relationships and narratives of the alien become limited by its adherence or lack thereof to the features of the dominant human. This manifests in how personhood is ascribed in media (according to gender performance, sexuality, race, physicality and other categories) to both aliens and their real-life reflection, the human other. Pilot culminates in an interactive intervention blending film, game and literature within a two-player character-driven narrative that discusses settler-colonialism, relationships and personhood through the lens of both the alien and the human other.
Keywords: Aliens in art; Characters and characteristics in art; Computer games; Design; Research Subject Categories::HUMANITIES and RELIGION::Aesthetic subjects::Art